Computer-assisted discovery of compounds with insecticidal activity against Musca domestica and Mythimna separata. (January 2021) - Soares Rodrigues, Gabriela Cristina; Maia, Mayara dos Santos; Silva Cavalcanti, Andreza Barbosa; Costa Barros, Renata Priscila; Scotti, Luciana; Cespedes-Acuña, Carlos L.; Muratov, Eugene N.; Scotti, Marcus Tullius
Abstract: Pesticides are used to control and combat insects and pests in the agricultural sector, households, and public health programs. The frequent and disorderly use of these pesticides may lead to variety of undesired effects. Therefore, natural products have many advantages over to synthetic compounds to be used as insecticides. The goal of this study was to find natural products with insecticidal potential against Musca domestica and Mythimna separata . To achieve this goal, we developed predictive QSAR models using MuDRA, PLS, and RF approaches and performed virtual screening of 117 natural products. As a result of QSAR modeling, we formulated the recommendations regarding physico-chemical characteristics for promising compounds active against Musca domestica and Mythimna separata . Homology models were successfully built for both species and molecular docking of QSAR hits vs known insecticides allowed us to prioritize twenty-two compounds against Musca domestica and six against Mythimna separata . Our results suggest that pimarane diterpenes, abietanes diterpenes, dimeric diterpenes and scopadulane diterpenes obtained from aerial parts of species of the genus Calceolaria (Calceolariaceae: Scrophulariaceae) can be considered as potential insecticidal. Highlights: Promising compounds active against Musca domestica and Mythimna separata . MuDRA, PLS, RF QSAR models using Volsurf descriptors and structure-based studies. Inhibitory activity against acetylcholinesterase and chitinase. Diterpenes from aerial parts of the Calceolaria as a potential insecticidal.